A Comparative Analysis of Regional and Local Anesthesia in Arteriovenous Fistula Surgery: A Single-Center Study - Mustafa Cüneyt Çiçek (Genel Tıp Dergisi)
Background: This retrospective study aimed to compare the outcomes of regional anesthesia and local anesthesia techniques in arteriovenous fistula operations, focusing on early patency rates, operation time, and postoperative pain. Methods: A total of 77 arteriovenous fistula and arteriovenous graft operations performed between April 2020 and April 2023 on adult patients with chronic renal failure were analyzed. The patients were divided into two groups based on the anesthesia technique: Group-1 (n=49) received local anesthesia, while Group-2 (n=28) received regional anesthesia. Results: The majority of operations in the local anesthesia group involved radio-cephalic arteriovenous fistula, while brachio-cephalic, brachio-basilic arteriovenous fistula, and arteriovenous grafts were predominantly performed in the regional anesthesia group. There was no significant difference in operation time between the two groups. However, the regional anesthesia group had a significantly lower need for pain relief within the first 24 hours postoperatively. There were no significant differences in early postoperative fistula failure or bleeding/hematoma between the groups. One case of local wound infection was observed in each group during post-discharge follow-up. Conclusion: This retrospective analysis suggests that regional anesthesia provides superior pain control in the first 24 hours following arteriovenous fistula surgery compared to local anesthesia. Regional anesthesia is a safe and effective technique and may be preferred for more sophisticated arteriovenous fistula procedures.